Prognostic Value of Tumor-Associated Macrophages in Clear Cell Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Shen, Haixiang; Liu, Jin; Chen, Shiming; Ma, Xueyou; Ying, Yufan; Li, Jiangfeng; Wang, Weiyu; Wang, Xiao; Xie, Liping (Frontiers in Oncology, 2021)
Background: Tumor-associated macrophages (TAMs) are the major immune cells in tumor microenvironment. The prognostic significance of TAMs has been confirmed in various tumors. However, whether TAMs can be prognostic factors in clear cell renal cell carcinoma (ccRCC) is unclear. In this study, we aimed to clarify the prognostic value of TAMs in ccRCC. Methods: We searched PubMed, Embase, and the Web of Science for relevant published studies before December 19, 2020. Evidence from enrolled studies were pooled and analyzed by a meta-analysis. Hazard ratios (HRs) and odd ratios (ORs) with 95% confidence intervals (CIs) were computed to evaluate the pooled results. Results: Both of high CD68+ TAMs and M2-TAMs were risk factors for poor prognosis in ccRCC patients. The pooled HRs indicated that elevated CD68+ TAMs correlated with poor OS and PFS (HR: 3.97, 95% CI 1.39-11.39; HR: 5.73, 95% CI 2.36-13.90, respectively). For M2-TAMs, the pooled results showed ccRCC patients with high M2-TAMs suffered a worse OS and shorter PFS, with HR 1.32 (95% CI 1.16-1.50) and 1.40 (95% CI 1.14-1.72), respectively. Also, high density of TAMs was associated with advanced clinicopathological features in ccRCC. Conclusions: TAMs could be potential biomarkers for prognosis and novel targets for immunotherapy in ccRCC. Further researches are warranted to validate our results.